The Effect of Product Descriptions, Online Customer Reviews, and Price Discounts on Impulse Buying Mediated by Ease of Purchase and Positive Emotion at Tiktok Shop Live - Juraidah (International Journal of Economics Accounting and Management, 2025)
This study aims to identify and analyze how product descriptions, online customer reviews, and price discounts affect impulse buying which is mediated by ease of purchase and positive emotion on TikTok Shop Live so that it can provide relevant insights for marketing academics and practitioners about consumer behavior in the modern e-commerce era. This study was conducted on TikTok Shop live users in Indonesia, using a quantitative approach. Data were collected through an online survey using a questionnaire designed based on a Likert scale, and analyzed using the SmartPLS-based Structural Equation Modeling (SEM) method. The results showed that product descriptions, online customer reviews, and price discounts have a significant influence on impulse purchases, both directly and through the mediation of ease of purchase and positive emotion. Informative and interesting product descriptions, positive customer reviews, and competitive price discounts increase the urge to buy impulsively. The mediating variables of ease of purchase and positive emotion strengthen this relationship by creating an easier and more enjoyable shopping experience. This research provides theoretical contributions by expanding the understanding of consumer behavior in the context of live shopping, as well as practical contributions for e-commerce businesses in designing effective marketing strategies to encourage impulse purchases through the interactive features of TikTok Shop Live